Vaginal-perianal or vaginal-perineal compared with vaginal-rectal culture-based screening for Group B Streptococci (GBS) colonization during the third trimester of pregnancy: a systematic review and meta-analysis - Hugh C. G. Nadeau; Courtney Bisson; Xi Chen; Yan D. Zhao; Marvin Williams; Rodney K. Edwards (BMC, 2022)
Abstract Background Screening for maternal anogenital Group B streptococci (GBS) colonization in pregnancy with initiation of intravenous intrapartum antibiotic prophylaxis as indicated has led to a significant reduction in the incidence of neonatal GBS infection. This study aims to evaluate the agreement between vaginal-perianal or vaginal-perineal culture and the more typically used vaginal-rectal culture for screening for maternal anogenital GBS colonization in the third trimester of pregnancy. Methods Eligible English-language studies published until January 2020 were retrieved from Scopus, Web of Science, PubMed, Embase, and ClinicalTrials.gov databases. Studies were compiled that assessed for GBS colonization utilizing vaginal-perianal or vaginal-perineal culture and vaginal-rectal culture during the third trimester of pregnancy. Nonoriginal research articles and studies that did not assess pregnant patients, did not use culture-based screening, or did not compare vaginal-perianal or vaginal-perineal culture with vaginal-rectal culture were excluded. The search identified 559 articles with three prospective cohort studies that met inclusion criteria, including 643 participants. Quality was assessed using the Newcastle-Ottawa Scale, and risk of bias was assessed using the Risk of Bias In Non-randomized Studies of Interventions (ROBINS-I) tool. Patient characteristics and associated pain with specimen collection were abstracted. Meta-analyses of both the raw agreement and the Cohen's kappa statistic were performed. Results Within the three included studies, the range of GBS detection was 17.6-34.0%, consistent with the anticipated prevalence of GBS colonization reported in earlier publications. For both raw agreement and Cohen's kappa coefficient, the test for heterogeneity was not significant, indicating low heterogeneity among studies. The pooled estimate of the raw agreement was 0.97 (95%CI 0.95-0.98) and of the Cohen's kappa coefficient was 0.91 (95% CI: 0.87-0.95), indicating (according to the Landis and Koch criteria) an "almost perfect" agreement between the compared clinical tests. In the two studies that assessed procedure-related patient discomfort, vaginal-rectal swabbing caused more discomfort. Conclusion Use of vaginal-perineal culture for assessment of maternal GBS colonization is comparable to the more typically utilized vaginal-rectal culture and is associated with less discomfort.